Improved Laser Damage Threshold of In(2)Se(3) Saturable Absorber by PVD for High-Power Mode-Locked Er-Doped Fiber Laser - Han, Xile (Nanomaterials (Basel), 2019)
In this study, a double-end pumped high-power passively mode-locked erbium-doped fiber laser (EDFL) was realized by employing a few-layered In(2)Se(3) flakes as a saturable absorber (SA). Herein, the uniform large-scale In(2)Se(3) flakes were synthesized by the physical vapor deposition (PVD) method. The PVD-In(2)Se(3) SA exhibited a remarkable damage threshold of higher than 24 mJ/cm(2). Meanwhile, the PVD-In(2)Se(3) SA had a modulation depth and saturable intensity of 18.75% and 6.8 MW/cm(2), respectively. Based on the In(2)Se(3) SA, the stable bright pulses emitting at 1559.4 nm with an average output power/pulse energy/pulse duration of 122.4 mW/5.8 nJ/14.4 ns were obtained successfully. To our knowledge, 122.4 mW was the new major breakthrough of mode-locked Er-doped fiber lasers. In addition, this is the first demonstration of the dark-bright pulse pair generation based on In(2)Se(3) SA. The maximum average output power of the dark-bright pulse reached 121.2 mW, which also showed significant enhancement in comparison with previous works. Our excellent experiment results fully prove the superiority of our experimental design scheme and indicate that the PVD-In(2)Se(3) could operate as a promising highly-nonlinear photonic material for a high-power fiber laser.